2008
DOI: 10.1182/blood-2007-09-110635
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed NF-κB–inducing kinase contributes to the tumorigenesis of adult T-cell leukemia and Hodgkin Reed-Sternberg cells

Abstract: The nuclear factor-B (NF-B) transcription factors play important roles in cancer development by preventing apoptosis and facilitating the tumor cell growth. However, the precise mechanisms by which NF-B is constitutively activated in specific cancer cells remain largely unknown. In our current study, we now report that NF-B-inducing kinase (NIK) is overexpressed at the pretranslational IntroductionThe nuclear factor-B (NF-B) transcription factors are known to regulate the expression of a wide range of genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 50 publications
2
103
0
Order By: Relevance
“…In support for a role of this pathway in lymphomagenesis, NIK is overexpressed in some cases of T-cell leukaemias and in Hodgkin's lymphomas that do not express any oncogenic viral proteins (Saitoh et al, 2008). Levels of p52 are also increased in those NIK overexpressing haematological disorders and levels of MMP9 are decreased on NIK depletion through RNAi interference in these cells (Saitoh et al, 2008). Thus, these data, combined with our report, suggest that MMP9 is a direct target gene of the NIK-and p100/p52-dependent signalling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In support for a role of this pathway in lymphomagenesis, NIK is overexpressed in some cases of T-cell leukaemias and in Hodgkin's lymphomas that do not express any oncogenic viral proteins (Saitoh et al, 2008). Levels of p52 are also increased in those NIK overexpressing haematological disorders and levels of MMP9 are decreased on NIK depletion through RNAi interference in these cells (Saitoh et al, 2008). Thus, these data, combined with our report, suggest that MMP9 is a direct target gene of the NIK-and p100/p52-dependent signalling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Primary MEFs were prepared from pregnant female mice on embryonic day 13.5, as described previously (4). To prepare bone marrow-derived dendritic cells, mouse bone marrow cells were cultured in the presence of 10 ng/mL GM-CSF (PeproTech) for 6 d, during which time the culture medium was replaced with medium containing GM-CSF every 2 d. The 293T cells have been described previously (46). Replication-competent MLV was produced by 293T cells transfected with pMLV-48.…”
Section: Methodsmentioning
confidence: 99%
“…As will be discussed below, HTLV Tax protein activates non-81 npg canonical NF-κB via a NIK-independent mechanism. However, the deregulation of NIK may be important for constitutive non-canonical NF-κB activation in ATL cells with low or undetectable levels of Tax [96].…”
Section: Deregulated Nik Stabilization and Expressionmentioning
confidence: 99%
“…It has been shown that the level of NIK mRNA is upregulated in adult T-cell leukemia (ATL) and Hodgkin Reed-Sternberg cells [96]. ATL is an acute T-cell malignancy caused by infection of the human T-cell leukemia virus type 1 (HTLV1).…”
Section: Deregulated Nik Stabilization and Expressionmentioning
confidence: 99%